Pengaruh Internalisasi Core Values Dan Employer Branding Terhadap Revolusi Mental Aparatur Sipil Negara - Marsikin Marsikin; Apri Budanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The hope for the ASN mental revolution is motivated by the gap between the expected performance (intended performance) and the actual performance produced (actual performance) by ASN. There are still many levels of inefficiency in carrying out tasks which is clear evidence of low competence. Civil servants who lack professionalism and lack moral awareness tend to abuse their authority or misuse state finances. This problem is used as an example that the ASN's mental revolution has not been fully successful, namely in carrying out tasks which are clear evidence of the commitment of the apparatus which is still low. This study aims to determine 1) the effect of internalizing core values ​​on the mental revolution of the State Civil Apparatus, 2) the effect of employer branding on the mental revolution of the State Civil Apparatus, and 3) the effect of internalizing core values ​​and employer branding on the mental revolution of the State Civil Apparatus at the District Secretariat. Cilacap. The research method used is descriptive quantitative method. Meanwhile, data collection techniques used questionnaires, and data analysis used multiple linear regression. The results of the study show that there is an influence between the internalization of core values ​​on mental revolution, there is an influence between employer branding on mental revolution, and there is an influence of internalization of core values ​​and employer branding on the mental revolution of the State Civil Apparatus at the Regional Secretariat of Cilacap Regency. This means that the more successful the internalization of core values ​​and employer branding, the higher the level of success of the mental revolution of the State Civil Apparatus.